Pengaruh Model Pembelajaran Self Regulated Learning Pada Mata Pelajaran Biologi Terhadap Literasi Sains Dan Sikap Ilmiah Siswa Kelas X SMAN 5 Kendari Sulawesi Tenggara - rosman sadat (Bioedusiana: Jurnal Pendidikan Biologi, 2019)
This study aims to describe the effect of Self Regulated Learning (SRL) Model in the Biology Subject on biodiversity topic on: (1) the science literacy (2) the scientific attitude, and (3) the science literacy and the scientific attitude of the students SMAN 5 Kendari. This research was a quasy experiment using pretest-posttest nonequivalent group designs. The study population was all students grade X MIA of SMAN 5 Kendari in the odd semester of the school year 2018/2019. Two sample classes were chosen randomly. On one side, the SRL model was used in the experimental class; on the other side, the direct instruction model was used in the control class. For the data collection techniques, test and inventory list were used. The test was used to determine the science literacy and the inventory list was used to determine scientific attitude of the students after participating in the SRL model with the topic of biodiversity. The data were analyzed using the independent sample t test and the multivariate (MANOVA) test with the significance level of 0,05. The results show that the SRL model has a significant effect on (1)  the science literacy, (2) the scientific attitude, (3) the science literacy and scientific attitude of the Students of SMAN 5 Kendari. In conclusion, the SRL model has a significant effect on the students’ science literacy and scientific attitude.Key word:Self Regulated Learning Model, science literacy, scientific attitude